2018
DOI: 10.1007/s13204-018-0774-0
|View full text |Cite
|
Sign up to set email alerts
|

Nano interface potential influences in CdTe quantum dots and biolabeling

Abstract: Nano interface influences in physiochemical properties of quantum dots (QDs) are the challenging approach to tailor its surface functionalities. In this study, a set of polar and non-polar solvents were selected to analyze the influences in solventbased dynamic radius and surface potential of QDs. From the nano interface chemistry of polar and non-polar solvents, an appropriate mechanism of precipitation and hydrophobic ligand exchange strategy were elucidated by correlating Henry's equation. Further, the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…These results indicated that both synthesized CDs were negatively charged, as in previous CD studies [16], however the PBS‐based CDs were coated with more negatively charged polar groups in comparison with the ethanol 20%‐based CDs. This fact probably is related to the chemical structure differences of their synthesis solvents, such as the amount of O − /O–H structures in each solvent [33] which was also confirmed by FTIR spectra. Concerning CDs morphology, AFM displayed a diameter of ~3 nm for the PBS‐based CDs and 5 nm for the ethanol 20%‐based CDs (Figure 1c).…”
Section: Resultsmentioning
confidence: 88%
“…These results indicated that both synthesized CDs were negatively charged, as in previous CD studies [16], however the PBS‐based CDs were coated with more negatively charged polar groups in comparison with the ethanol 20%‐based CDs. This fact probably is related to the chemical structure differences of their synthesis solvents, such as the amount of O − /O–H structures in each solvent [33] which was also confirmed by FTIR spectra. Concerning CDs morphology, AFM displayed a diameter of ~3 nm for the PBS‐based CDs and 5 nm for the ethanol 20%‐based CDs (Figure 1c).…”
Section: Resultsmentioning
confidence: 88%
“…However, some electrons at the 4 F 9/2 level can be further excited to the 2H 9/2 level or electrons at the 4 G 11/2 level non-radiatively relax to the 2 H 9/2 level, as described in Fig. 6b (7), (8). Subsequent radiative decay of the excited electrons at the 2 H 9/2 level to the 4 I 15/2 should lead to the enhancement in the peak intensity of the peak at 414 nm.…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…With the recent advances in nanotechnology and molecular biology, nanobiotechnology has developed rapidly over the past few years [1][2][3]. In particular, the design and development of multifunctional nanomaterials for biomedical applications provide an unprecedented opportunity for simultaneous diagnosis and therapy of diseases [4][5][6][7][8]. Indeed, luminescent nanomaterials, including Si nanoparticles [6], semiconducting quantum dots [8,9], carbon dots [10], and nanodiamonds [11], have recently attracted a great deal of interest for biomedical imaging, diagnose and diseases therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photophysical properties of CQDs help to obtain photokilling effect to control bacterial growth via photoinduced redox oxidation process (Dong et al, 2017). The recent study suggests that surface charge‐based interaction of CQDs with microbes can induce potential antibacterial activity on other hand neutral charge CQDs were inefficient (Kanagasubbulakshmi & Kadirvelu, 2018). Though the CQDs possess less toxicity on the animal cells, the antibacterial activity surprises the researchers due to its size‐ and charge‐based interaction with the microbial system.…”
Section: Introductionmentioning
confidence: 99%